Compromise - Knight, Jack, 1952- (Nomos ;, 2018)
"Childhood friends Juliet, Rebecca, Rose and Matthew grew up in a small village outside Dublin. Now privileged, wealthy and powerful, they appear to have it all. But when Juliet is involved in a suspicious accident and lies trapped between life and death at the bottom of a cliff, a secret that has been hidden for years threatens the seemingly perfect lives of the close-knit group. For the beautiful, fragile Rose, Juliet's accident draws unwanted attention to the sins of the past. For her husband, the ruthlessly ambitious Matthew, it removes a critical obstacle from the path of his political career. And as Rebecca discovers more about what happened to her friend, she begins to wonder if she ever knew the real Juliet ..."--Publisher description.